Exploration of the mechanism underlying the therapeutic effect of electroacupuncture at chengshan acupoint on post-hemorrhoidectomy anal pain: Insights from the mAChRs/IP3-Ca2+-CaM signaling pathway - Song, Yang (2024)
Objective: In the context of postoperative anal pain, understanding the intricate mechanisms and effective interventions is paramount. This study investigates the role of Muscarinic Acetylcholine Receptors (mAChRs) and the IP3-Ca2+-CaM signaling pathway in a rat model of postoperative anal pain, exploring the potential analgesic effects of electroacupuncture. Methods: Comprehensive approaches involving mechanical sensitivity assays, Western blotting, immunohistochemistry, and intracellular calcium concentration measurement were used. Results: The authors found elevated mAChRs expression in the postoperative pain model. Antagonizing mAChRs reduced pain sensitivity and attenuated the IP3-Ca2+-CaM pathway. Remarkably, electroacupuncture treatment further mitigated pain, potentially by suppressing this signaling cascade. Interpretation: These findings reveal a novel connection between mAChRs and the IP3-Ca2+-CaM pathway in postoperative anal pain and suggest electroacupuncture as a promising avenue for pain relief through these mechanisms, offering insights into innovative strategies for postoperative pain management.